Maharah Qira’ah Assessment Innovation with Receptive Active Language Competency Test - Mustika Dewi, Azzaria Mida; Baroroh, R. Umi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
Evaluation of teaching materials shows that the presentation is systematic, coherent, consistent and balanced between chapters. In terms of supporters, the presentation does not contain a complete list of supporters, there are deficiencies in the evaluation of maharah qira'ah. The purpose of reading is to understand the text being read and the content of the text gives meaning to the reader. The purpose of this study is to see the assessment of Arabic textbooks in 2020 published by the Ministry of Religious Affairs of the Republic of Indonesia in accordance with the criteria for learning maharah qiraah. The method used in this research is a literature study with a descriptive qualitative approach. The source of the data obtained comes from class VIII Arabic textbooks in 2020 published by the Ministry of Religious Affairs of the Republic of Indonesia as well as journals, books, and so on. Data analysis techniques by collecting and interpreting data then describing it. The results of this study state that maharah assessment has not provided a form of test that describes understanding for readers both orally and in writing. So, it is good that maharah kitabah in class VIII Arabic textbooks in 2020 published by the Indonesian Ministry of Religious Affairs needs to improve their assessment techniques.